Analysis of the Potential Mechanism of Sanhua Decoction in Treating Ischemic Stroke Based on Network Pharmacology and Molecular Docking Technology - Zhao, Wei; Li, Dan; Yue, Min; Yan, Cheng; Li, Feng; Qi, Yonghua (Chinese medicine and natural products, 2024)
Objective The aim of this study was to explore the action mechanism of Sanhua decoction in treating ischemic stroke through network pharmacology and molecular docking technology.Methods Active components and related targets of Sanhua decoction were obtained from the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform. A “drug-active component-target” network was constructed, and core components were selected through topological analysis. Disease targets related to ischemic stroke were screened based on the Online Mendelian Inheritance in Man (OMIM), Therapeutic Target Database (TTD), GeneCards, DrugBank, and PharmGKB databases. The intersection of active component–related targets and ischemic stroke disease targets was identified to obtain potential targets of Sanhua decoction for treating ischemic stroke, represented using a Venn diagram. The STRING database was used to construct a protein–protein interaction (PPI) network of potential targets and filter for core targets. Gene Ontology (GO) functional enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis of core targets were performed using the DAVID database and Metascape platform. Molecular docking verification of core targets and core components was conducted using AutoDock.Results A total of 52 active components and 142 related targets were screened from Sanhua decoction, with core active components including luteolin, nobiletin, β-sitosterol, eucalyptol, and aloe-emodin. There were 2,991 ischemic stroke–related targets, with 98 potential targets identified in the intersection with active component–related targets. An analysis of the PPI network analysis revealed 23 core targets, including serine/threonine-protein kinase 1 (AKT1), tumor protein p53 (TP53), and mitogen-activated protein kinase 3 (MAPK3). Enrichment analysis obtained 35 GO results and 41 signaling pathways. Molecular docking results indicated good binding between core components and core targets.Conclusion Multiple components in the classic formula Sanhua decoction, such as luteolin and nobiletin, may play a role in treating ischemic stroke by regulating core targets like AKT1, TP53, and MAPK3, and participating in multiple signaling pathways.
Keywords: Sanhua decoction; ischemic stroke; network pharmacology; molecular docking technology